Public Development Banks and fintech in a business environment that advances digital financial inclusion for micro and small businesses: a conceptual framework based on Brazilian context - Melo, Rogerio de Castro; Tavares, Elaine; Diniz, Eduardo Henrique (Cadernos do Desenvolvimento, 2024)
This work aims to study how Public Development Banks (PDBs) and fintech can amplify digital financial inclusion for micro and small businesses, companies that suffer worldwide from credit restrictions to grow their business and even to survive during times of crisis. PDBs, which are key actors in the development finance, are partnering with fintech, companies that bring the promise to advance digital financial inclusion. Brazil has about 17 million small businesses, a strong fintech business environment, and one of the major PDBs, the Brazilian Development Bank (BNDES). Thus, driving on Brazilian context, based on a fintech business environment literature review, and selected PDBs and Brazilian small businesses secondary data analysis, we propose a theoretical framework that can help to advance digital financial inclusion for small businesses, contributing to scholars, policymakers, and other Global South economies to reduce social inequalities acting as a shortcut to achieve Sustainable Development Goals.